2016
DOI: 10.1021/acs.inorgchem.6b01477
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Tricarbonyl Complexes with Asymmetric 2-Iminopyridine Ligands: Toward Decoupling Steric and Electronic Factors in Electrocatalytic CO2 Reduction

Abstract: Manganese tricarbonyl bromide complexes incorporating IP (2-[(phenylimino)]pyridine) derivatives, [MnBr(CO) 3 (IP)], are demonstrated as a new group of catalysts for CO 2 reduction, which represent the first example of utilization of phenylimino pyridine ligands on manganese centers for this purpose. The key feature is the asymmetric structure of the redox non-innocent ligand that permits independent tuning of its steric and electronic properties. The -diimine ligands and five new Mn(I) compounds have been syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 53 publications
10
40
0
Order By: Relevance
“…NMR analysis of single crystals that were analysed by X-ray crystallography showed that the intense signal at 42.2 ppm can be assigned to the isomer found in the solid state (see below). The IR spectrum of (4) shows three pronounced carbonyl-stretching vibrations at 2008, 1952, and 1911 cm À1 , in line with values for other Mn I tricarbonyl complexes (Spall et al, 2016).…”
Section: Figuresupporting
confidence: 80%
“…NMR analysis of single crystals that were analysed by X-ray crystallography showed that the intense signal at 42.2 ppm can be assigned to the isomer found in the solid state (see below). The IR spectrum of (4) shows three pronounced carbonyl-stretching vibrations at 2008, 1952, and 1911 cm À1 , in line with values for other Mn I tricarbonyl complexes (Spall et al, 2016).…”
Section: Figuresupporting
confidence: 80%
“…Currently, much of the literature regarding molecular electrochemical activation of CO 2 still continues to explore the catalytic properties of the heavier members of Group‐7 (Re), Group‐8 (Ru and Os) and Group‐9 (Rh, and Ir) triads. These “first‐generation” electrocatalysts must be phased out; encouragingly, cheaper alternatives exist within the same groups – Mn substituting Re, Fe substituting Ru and Os, and Co substituting Rh and Ir . However, the community's focus on late transition metals is leaving the Group‐6 metals (Cr, Mo, W) rather neglected, despite the high potential for the comparatively abundant metal triad to function as both high‐performance alternatives to the noble metals and photostable alternatives to the hot‐topic manganese carbonyls .…”
Section: Methodsmentioning
confidence: 99%
“…Highly promising are the systems of [Mn(CO) 3 )(α-diimine)X] (X = (pseudo)halide), only recently found to be catalytically active at potentials similar to the analogous complexes of rhenium, in the presence of Brønsted or Lewis acids. [22][23][24][25][26][27][28] The Fe-porphyrin systems are also highly efficient catalysts of CO 2 reduction, but synthetically challenging to prepare. [29][30][31] Surprisingly, and despite the analogues found in Nature, the Group-6 metal triad (Cr, Mo, W) has largely been ignored by the wider community.…”
Section: Introductionmentioning
confidence: 99%